Design, synthesis, and bioactivity investigation of novel benzimidazole derivatives as potent urease inhibitors. Issue 1 (2nd January 2022) - Saeedian Moghadam, Ebrahim; Al-Sadi, Abdullah Mohammed; Talebi, Meysam; Amanlou, Massoud; Amini, Mohsen; Abdel-Jalil, Raid
Abstract: Herein, we synthesized a series of novel benzimidazole derivatives 5a–k and screened their bioactivity as potent urease inhibitors. The structure of the 5a–k was elucidated using spectroscopic technics ( 1 H-NMR, 13 C-NMR, MS), elemental analysis, and melting point. The urease inhibition activity was evaluated using the urease enzyme inhibition kit. All 5a–k, except 5d, showed higher urease inhibition activity (0.77 to 6.25 µM) in comparison to thiourea and hydroxyurea as standard (IC50: 22 and 100 µM respectively). 5c and 5j exhibited the best activity with the IC50 value of 0.77 and 1.26 µM respectively. A molecular docking study showed the mode of interactions between the most active compound and enzyme active site. To investigate the cytotoxicity profile of the target compounds, an MTT assay was done on two different cell lines which showed all 5a–k have IC50 values higher than 50 µM on both tested cell lines. Graphical Abstract: UF0001